ВСЁ ПУТЁМ: ТЕКСТИЛЬНАЯ ПУТИНИАНА КАК КОНТЕКСТУАЛЬНО ОБУСЛОВЛЕННЫЙ ПРОДУКТ - Sładkiewicz, Żanna (Przegląd Rusycystyczny, 2017)
The paper deals with the notion of context and its typology. The author analyzes modern prints on T-shirts representing Vladimir Putin as the product conditioned by the current socio-political context. The article presents the linguistic and rhetorical methods as well as graphical representation of the image of the President of Russia in the phatic genre of public communication, which is print on clothes.